2020
DOI: 10.1159/000507711
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Data in the Treatment of Neovascular Age-Related Macular Degeneration: Results from the Imaculaweb Registry Evaluated in a Single Italian Medical Retina Center

Abstract: Introduction: The aim of this study is to assess and compare the long-term clinical efficacy of anti-VEGF drugs using the Imaculaweb registry. Methods: In this observational study based on the Imaculaweb registry, outcome measures were the number of injections, the change in mean visual acuity (VA) and central macular thickness (CMT), and the time between diagnosis and the first injection. Results: In total, 126 eyes of 109 patients were included in the study. The mean VA was 49.4 ± 21.4, 54.1 ± 22.2, 51.6 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Unfortunately, relevant statistical studies have found that patient compliance is decreasing every year. Such as in one study, it was reported that the injection numbers were 5.2, 2.6, and 2.3 at the 1-, 2-, and 3-year follow-ups, respectively ( 19 ), affecting treatment outcomes. Therefore, the development of new treatment directly acts on HMECs options is of particular importance.…”
Section: Introductionmentioning
confidence: 96%
“…Unfortunately, relevant statistical studies have found that patient compliance is decreasing every year. Such as in one study, it was reported that the injection numbers were 5.2, 2.6, and 2.3 at the 1-, 2-, and 3-year follow-ups, respectively ( 19 ), affecting treatment outcomes. Therefore, the development of new treatment directly acts on HMECs options is of particular importance.…”
Section: Introductionmentioning
confidence: 96%
“…The practice of intravitreal injection (IVT) with anti-vascular endothelial growth factor (VEGF) has significantly impacted the outcomes of exudative macular diseases in recent years and nowadays represents the most frequently performed ocular procedure [1][2][3][4]; moreover, the frequency of this procedure is growing worldwide and, in parallel, the risk of procedure-related complications [5]. Among them, endophthalmitis, the most fearful ocular complication, has a reported incidence ranging from 0.019% to 0.083% [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to intensive glycemic control, the management of DME requires multidisciplinary care, including intravitreal anti-vascular endothelial growth factor (VEGF) drugs, intravitreal corticosteroids, laser photocoagulation, and vitrectomy [3,4]. Currently, intravitreal anti-VEGF drugs are mostly regarded as first-line therapy [5][6][7]. However, a significant number of DME patients do not respond to anti-VEGF drugs, and non-VEGF mediators are urgently needed for these patients [8].…”
Section: Introductionmentioning
confidence: 99%